Peran igf-1 dan let-7 dalam morfogenesis gigi ditinjau dari sel punca mesenkimal pulpa gigi - Endriyana, Jessica; Aryani Hayuningtyas, Ria (Jurnal Kedokteran Gigi Terpadu, 2024)
Tooth development is a complex process involving the interaction between dental epithelium and mesenchymal tissues. IGF-1 plays a crucial role in regulating cell proliferation, differentiation, apoptosis, and migration. Its significance is particularly notable during the proliferation and differentiation stages of root development, as well as in the stem cells derived from the apical papilla responsible for root pulp and dentin formation. IGF-1 exhibits osteoconductive potential in bone healing by modulating osteoclasts in bone resorption and osteoblasts in bone formation. Stem cells from dental pulp or apical papilla represent a mesenchymal stem cell or progenitor population that forms calcium nodules in osteo/odontogenic media. This study aims to elucidate the roles of IGF-1 and Let-7 in tooth morphogenesis, utilizing the PRISMA guidelines for data collection. A total of 12 literature sources were identified, with 3 articles published in the last 5 years. Only 5 articles were selected for inclusion in this study. Further exploration of IGF-1/IGF-1R/hsa-let-7c modulation in odonto/osteogenic differentiation holds promise for future tooth regeneration. IGF-1 enhances the size of tooth bud cultures, suggesting potential applications in genetic engineering for tooth morphogenesis. IGF-1 plays a crucial role in odontogenic proliferation and differentiation.